P34 Paramedic trail blazers – why do paramedics take part in prehospital research?. (September 2018) - Evans, BA; Brown, A; Bulger, J; Fegan, G; Ford, S; Guy, K; Jones, S; Keen, L; Rees, N; Snooks, H
Abstract : Background: Research to improve prehospital treatment and care requires the participation of clinical and managerial staff from ambulance services to test interventions and collect research data. Researchers work closely with individuals and organisations with prehospital clinical, managerial and policy expertise to plan, deliver and disseminate research evidence. A recent trial involved assessing feasibility of paramedics administering Fascia Iliaca Compartment Block (FICB) in place of morphine to patients with suspected hip fracture. Participation in the trial was voluntary. We explored paramedics' motivation for participating in research through the RAPID (Rapid Analgesia for Prehospital Hip Disruption) trial. Methods: We held three focus groups with 11 RAPID trial paramedics serving one district hospital, audio-recorded with participants' consent. We conducted thematic analysis of interview transcripts. Two researchers, one paramedic and one lay member were in the analysis team. Results: Paramedics believed their participation in research had benefits for patients, for them individually and for the paramedic profession. Respondents said that being part of a research project provided an opportunity to increase their skills and provide improved patient care. In the RAPID trial, they understood the potential risks and benefits of different medications and management for patients with suspected hip fracture and welcomed the chance to identify improved pain management for a vulnerable population. They felt proud to be learning and using a procedure usually administered by clinical staff: 'This is quite specialised, like, hang on, I'm doing a really top job here, dealing with anaesthetics…blunt needles… it's like 'up there'. It's not our everyday thing.' More generally, respondents identified how research potentially contributed towards widening the scope of paramedic practice by extending their role into clinically specialist areas. They suggested that many paramedics were unwilling to undertake tasks perceived to exceed their pay-grades and shunned the opportunity to learn new techniques which were not routine care. In comparison, these paramedics saw themselves as trail-blazers for the profession, proud to be acquiring extra clinical responsibilities and skills. They also valued the chance to contribute to the evidence base, providing knowledge about using alternative medication which they instinctively felt would cause fewer complications and benefit patient mortality and morbidity. Conclusion: Paramedics who take part in research believe they contribute to personal and professional development and potentially improve patient care. Future research with paramedics refusing research participation could explore barriers and different views on skills development, which may also inform implementation of new evidence-based interventions.